Exploring Factors Affecting Motivation in an English Classroom in the first year at university of Tabuk - Rahaf M. Altoweerqi; Nadyh N. Alawfi (Journal of Arts, Literature, Humanities and Social Sciences, 2024)
This research explores the influencing factors in motivation of first-year students to learn English at the University of Tabuk. By using a quantitative survey method, 300 first-year students at Tabuk University participated in this study by completing a questionnaire. The results show a variety of attitudes and perceptions among the students concerning their preferences for course materials, beliefs about learning effectiveness, attitudes toward academic achievement, and experiences of test anxiety. Majority of the students have a preference on course materials that are challenging provided that they foster curiosity and deeper engagement. Most students are confident in their capability in understanding course materials through exerting maximal effort and effective study habits. However, a significant number of students experience examinations anxieties and distress, which shows that such incidents are common. Furthermore, students have shown that they are motivated to achieve academic success so that they could showcase their abilities to their social and professional peers. Students remain confidence in their ability to have high academic performance despite course difficulty and doubts of their own skills, which demonstrate that they are resilient and are very adaptive with their learning. Such findings indicate that students’ attitudes are important. It also shows that their learning perception plays a central role in their motivation and engagement level within the academic environment thus providing the necessary guidance to establish effective pedagogies and necessary interventions. This will improve the motivation and engagement level of the students that are enrolled in English language courses.